Afetividade da família migrante: um estudo sociodramático - Oliveira, Susana Kramer de Mesquita (2008)
This is a case study with clinical-qualitative orientation? and in prominence (especially) socio-cultura questions, these elements found resonance in moreno's sociodramatic model (1992b, 1994a, 1994b). The purpose of this study was to theorically? and methodologically argue the emerging processes of social reinsertion of migrant families, combining clinical and socio-cultural questions relating to the study of familiar affectivity . The formation creation of the object in study ("the affectivity of the migrant family") came about through the interation among the family, migration, and affetctivity categories, in which affectivity is considered in its relational/mediatorial situation, which evidences the socio cultural aspects of migration, and postulates the family from its constituent characterustics while social group with history and a specific identify. In this way, the grouping processes (familiarity) of two northwestern families which reside in Brasílian were analyzed, primarily taking into account, their history of migration, from the sociodramatic work done with these two families at the same time ans is one single group. The Socionomy contributed concepts such as "Social Atom" and "Matriarch of Identity," established because of the vision of founded man, and at the same time, in ample social and cultural forces and, still, inthe microgenetic of specific affective relations, which confers great application to the "Morenian" project in these so called postmodern times. The Sociodrama method favored perception/comprehension of of the socio-familiar ralating (pertaining) modes. Its specific conditions were identified as much on the familiar nucleus's micro dimension, as in the amplified social domain, in which the subjects interacted affectively, socially, and culturally. The subjects participated as onde group, in four socio-dramatic sessions which aimed (sought) to identify: the dynamic of participancy, the idealized imagens of family.